Croatia - Karavanić, Ivor; Komšo, Darko; Vukosavljević, Nikola (2013)
In this article we present recent research on Upper Palaeolithic sites in Croatia from 2006. to 2010. We also present some new interpretations of material that has been excavated earlier.
Projekt MZOS
ENG